The Analysis of PM¹°Dust Exposure to the Labors Capacities’ Lungs in the Wooden Furniture Industry - Ramadani, Cica; Dewata, Indang; Candra, Naldi (European Journal of Life Safety and Stability (2660-9630), 2022)
This paper examines the correlation between exposure to wood dust, especially PM¹°, and decreased lung function. The effects of inhalation of particulate dust (PM¹°) have been widely studied in humans, plants, and animals. Issues of the impact include an increase in people with asthma and lung cancer and premature death. The research was done in August - December 2019 in three wood furniture industries in Pesisir Selatan Regency. This research is the main task and function of the author as a form of community service in occupational safety and health service activities. This study uses quantitative methods using the Chi-Square test. but, for other variables (age and years of service with impaired lung function) logistic regression analysis was used. The statistical analysis of the data shows that there is a significant relationship between the concentration of PM¹° and lung function in labor as seen from the FEV1 and FVC values between before and after work. Testing PM¹° concentration in furniture labor is carried out early so that it does not progress to Chronic Obstructive Pulmonary Disease (COPD).